Pengaruh eksipien terhadap sifat fisik granul effervescent : Review - Pratama, Reza; Munir Alinu Mulki; Saputro, M. Ramadhan; Afifah Rusyda Sani; Ratu Siti Robiatul Awaliyah (An-Najat, 2024)
The use of various plant species, which are then formulated using pharmaceutical technology in the form of effervescent granule preparations, is a strategy to increase the practicality and public interest in consuming herbal medicines. The natural ingredients most commonly used as the main ingredients in the manufacture of effervescent granules include fruits, rhizomes, fruit peels, leaves and seeds. Effervescent granules are a mixture of acidic and alkaline compounds which, when added to water, produce a carbon dioxide reaction. This creates a foam that gives a fresh taste effect and can mask unwanted flavours. The purpose of this article is to provide information on the formulation and evaluation of effervescent granules from various plant extracts that may have public health benefits. The method used to collect the data was a search of several journals. The results of the search showed the influence of excipients on the physical properties of the granules. These include organoleptic properties, flow time, dissolution time, water content and pH of effervescent granule preparations.